Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
https://doi.org/10.13016/M2QR4NT6S
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

De l’homosexualité à l’opéra - Champagne, Éric (L’Opéra : revue québécoise d’art lyrique, 2016)
Créée à l’Opéra de Montréal, l’œuvre de Kevin March, Les Feluettes, sur un livret de Michel Marc Bouchard, aborde de front une histoire d’amour entre deux hommes. Si les sujets homosexuels nous semblent communs dans la littérature, le théâtre et le cinéma, il faut se rendre à l’évidence qu’ils sont, du moins jusqu’à tout récemment, peu présents dans le monde de la musique, tous styles confondus. On entend beaucoup dire ces jours-ci que le genre de l’opéra, au public réputé conservateur, ne s’intéresse à cette thématique que depuis peu. Il s’agit en fait d’une demi-vérité, car s’il est vrai que l’homosexualité comme sujet principal n’est présent explicitement que dans des créations récentes, il se retrouve occasionnellement, caché ou crypté, dans diverses œuvres qui traversent son histoire vieille de plus de 400 ans.
https://www.revuelopera.quebec/ressources/revues/LOperaNo08_ETE2016.pdf
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; arts; discipline; histoire et politique; homosexualité; musique; périodes historiques; ressource en ligne; sexualité; sofia; thématiques